Unemployment insurance in welfare states: soft constraints and mild sanctions - Knut Røed; Lars Westlie (Institute for the Study of Labor (IZA), 2007)
Based on a sequence of reforms in the Norwegian unemployment insurance (UI) system, we show that activity-oriented UI regimes - i.e., regimes with a high likelihood of required participation in active labor market programs, duration limitations on unconditional UI entitlements, and high sanction probabilities - deliver substantially shorter unemployment spells than pure income-insurance regimes. Soft constraints, in the form of activity requirements or small benefit cuts after a pre-specified UI duration, have many of the same behavioral consequences as threats of complete benefit termination. Early introduction of a soft constraint appears particularly effective; our results show that the expected unemployment duration falls by half a day for each week the soft constraint is moved ahead in the UI spell. Mild sanctions, in the form of temporary benefit terminations in response to inadequate search effort or excess choosiness, cause a significant rise in the job hazard.
Keywords: 330; Arbeitslosenversicherung; Arbeitsmarktpolitik; Arbeitsuche; Arbeitslosigkeit; Dauer; Norwegen